2012
DOI: 10.5296/jbls.v4i1.2408
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Lactic Acid Bacteria Strains Isolated from Nile Tilapia Intestine (Oreochromis niloticus)

Abstract: The intestinal microflora of Nile tilapia (Oreochromis niloticus) fish was studied to isolate and identify lactic acid bacteria as new probiotic. A total of five lactic acid bacteria were isolated from intestine to evaluate with antibacterial properties. These strains were identified by conventional and molecular techniques as: Enterococcus faecium, Leuconostocmesenteroides, Lactobacillus fermentum, Lactobacillus plantarum, Enterococcus durans. Leuc.mesenteroides present more ability to inhibit growth of fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…These strains were similarly isolated from the gut of the Nile tilapia (Zapata and Lara-Flores, 2012). The findings are in agreement with (Ringø et al, 1997) who found that 10% microbiota population in Artic charr (Salvelinus aplinus L.) was lactic acid bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…These strains were similarly isolated from the gut of the Nile tilapia (Zapata and Lara-Flores, 2012). The findings are in agreement with (Ringø et al, 1997) who found that 10% microbiota population in Artic charr (Salvelinus aplinus L.) was lactic acid bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…A number of reports have confirmed that LAB are normal flora in gastrointestinal tract of healthy animals like mammals and aquaculture animals including fish [ 16 ] with no harmful effects [ 17 ]. Probiotics improve intestinal microflora with health beneficial efficacy protecting them against infections by stimulating the immune system, as well as alleviate lactose intolerance, reduce blood cholesterol levels, improve weight gain and feed conversion ratio [ 18 – 21 ]. Isolation of LAB from variety of samples has raised debate over the safety of probiotic bacteria and whether or not the bacteria are actually infectious [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on antibacterial activity Bacillus sp., Enterobacter sp., Aeromonas sp., (G1), (G3), (G4) has shown higher inhibition against pathogens Staphylococcus aureus, Shigella sonnei, Enterococcus faecalis, Pseudomonas aeruginosa and Klebsilla pneumoniae. Zapata et al (2013) reported that Lactic acid bacterial strains isolated from Nile Tilapia intestine showed the high ability to inhibit the growth of freshwater fish pathogen particularly Vibrio sp. and Mycobacterium sp.…”
Section: Resultsmentioning
confidence: 99%